Pharmacologic normalization of pathogenic dosage underlying genetic diseases: an overview of the literature and path forward. Issue 1 (18th March 2019) - Poirier, Mathieu B.; Hadwen, Jeremiah; MacKenzie, Alex
Abstract: Most monogenic disorders are caused by a pathologic deficit or excess of a single transcript and/or protein. Given that small molecules, including drugs, can affect levels of mRNA and protein, the pharmacologic normalization of such pathogenic dosage represents a possible therapeutic approach for such conditions. Here, we review the literature exploring pharmacologic modulation of mRNA and/or protein levels for disorders with paralogous modifier genes, for haploinsufficient disorders (insufficient gene-product), as well as toxic gain-of-function disorders (surplus or pathologic gene-product). We also discuss challenges facing the development of rare disease therapy by pharmacologic modulation of mRNA and protein. Finally, we lay out guiding principles for selection of disorders which may be amenable to this approach.